Delay estimation for some stationary diffusion-type processes - Uwe Küchler; Yuri A. Kutoyants (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
In this paper the asymptotic behaviour of the maximum likelihood and Bayesian estimators of a delay parameter is studied. The observed process is supposed to be the solution of a linear stochastic differential equation with one time delay term. It is shown that these estimators are consistent and their limit distributions are described. The behaviour of the estimators is similar to the behaviour of corresponding estimators in change-point problems. The question of asymptotical efficiency is also discussed.
urn:nbn:de:kobv:11-10057007
Keywords: 330; Stochastic Differential Delay Equations; Diffusion-type process; Estimation of Delay; Asymptotic Properties for Large Sample Size; Asymptotic Efficiency